From ‘intuitive’ pragmatic interventions to a systematic approach e Using implementation science to improve childhood cancer survival in low-income settings: The CANCaRe Africa experience - Israels, Trijn; Atwiine, Barnabas; Duffy, Caitlyn; Sichali, Junious; Afungchwi, Glenn; Pritchard-Jones, Kathy; Nyirenda, Deborah; Mwapasa, Victor (Pediatric Hematology Oncology Journal, 2024)
Implementation science is a relatively young field of study and is the science of delivering evidence based interventions into routine health care. RE-AIM (Reach, Effectiveness, Adoption, Implementation, and Maintenance) is an evaluation-type implementation science framework. CANCaRe Africa is preparing a project to assess the implementation and effectiveness of a cash incentive intervention to support families with out-of-pocket costs to prevent treatment abandonment and increase childhood cancer survival in sub-Saharan Africa. Our strategy is to enhance the dissemination of our research findings to local policymakers who can support the scale-up of evidence-based clinical interventions and locally effective implementation strategies. It can be done best by embedding implementation science into our clinical research approaches.
Keywords: Childhood cancer; Survival; LIC; Implementation science